Harmonising environment and development in South Asia - Wijayadasa, K. H. J. (South Asia Co-operative Environment Programme, 1997)
Contributed articles presented at the Environmental Management Seminar for South Asia in collaboration with United Nations Environment Programme, Norwegian Agency for Development Co-operation and Govt. of Sri Lanka at Colombo from 16-27 September, 1996.